Communication Audit within the Occupational Health and Safety System with an Ergonomics Approach at Dr. Rivai Abdullah Palembang Regional General Hospital - Asri, Mauliana; Misnawati, Desy; Hafizni, Mohamad; Zinaida, Rahma Santhi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
The communication audit becomes a comprehensive and in-depth study of the implementation of the organizational communication system aimed at improving the effectiveness of RSUP Dr. Rivai Abdullah Palembang. RSUP Dr. Rivai Abdullah Palembang is one of the healthcare institutions that is essential for supporting health factors in the community. The purpose of this research is to understand the ergonomic approach and communication audit in the services provided by RSUP Dr. Rivai Abdullah Palembang. The theoretical frameworks used in this study are the Laswell model and organizational theory. A qualitative research method with a case study approach is employed. The data sources include primary and secondary data, where primary data is gathered through interviews and secondary data consists of documentation and literature review. The findings of the study indicate the following: 1) there is an increased workload on employees and insufficient facilities at RSUP Dr. Rivai Abdullah Palembang, 2) lack of infrastructure facilities (media) in delivering services to patients, 3) suboptimal information delivery to patients, 4) ineffective facility arrangement, and 5) RSUP Dr. Rivai Abdullah Palembang applies the 5R concept but lacks a background in occupational health and safety (K3).